Temples, hoards and pre(?)monetary practices – Case studies from Mainland Italy and Sicily in the 1st millennium B.C. - Murgan, Andreas; Kemmers, Fleur (Materielle Kultur und Identität im Spannungsfeld zwischen mediterraner Welt und Mitteleuropa. Material Culture and Identity between the Mediterranean World and Central Europe. Akten der Internationalen Tagung am Römisch-Germanischen Zentralmuseum Mainz, 22.-24. Oktober 2014 Abschlusstagung des DFG-Projekts »Metallfunde als Zeugnis für die Interaktion zwischen Griechen und Indigenen auf Sizilien zwischen dem 8. und 5. Jahrhundert v. Chr.«, 2016)
Chunks, lumps and bars of different metal alloys are often thought to have served premonetary functions. But what exactly is the role of these objects, how, where and when were they used, and do they differ from coinage in these aspects? This paper seeks to address these questions by focusing on pre(?)monetary material from a selected number of case studies in mainland Italy and Sicily. In the first millennium B.C., it was a widespread tradition to deposit these valuable objects at selected places. The reasons therefore were manifold. On the one hand, the decision to deposit objects could have been ritually motivated, when the valuables were dedicated at holy places like temples, as a gift for a deity. On the other hand, profane reasons could also lead to a deposition, when people wanted to hide their valuables and store them securely, by burying them as a treasure in the earth. Depending on the context, the (pre) monetary pieces were used in conjunction with different other objects, while being involved in diverse ritual or profane activities. All of these features offer interesting insights into the behaviour of ancient people with (pre)monetary objects that could oscillate in their functions and meanings between profane money and ritual dedication. It is argued that the universality, continuity and widespread distribution of this material can be linked to its anonymous character, this in strong contrast to early coinage.